Computer simulation of high-current diode: from field emission to space charge limited current flow - Manuilenko, O.V.; Karas, V.I.; Kornilov, E.A.; Vinokurov, V.A.; Antipov, V.S. (Вопросы атомной науки и техники, 2015)
The results of numerical simulation of electron beam dynamics in the high-current diode with a blade-like cathode, which operates in the field emission regime, are presented. The computer simulations were performed by particle-in-cell method in the electrostatic approximation. It is shown that there are two modes of diode operation. In the first operation mode the space charge in the diode gap insignificant. In this case the anode current is small, and its value is determined by the Fowler-Nordheim law. This mode, with increasing potential difference between the cath-ode and the anode, passes in a mode of the space charge limited diode current. In this case the anode current is determined by the Child-Langmuir law. It is shown that the electron energy distribution function at the anode is almost monochromatic, with a maximum, which is determined by the potential difference between the cathode and the anode. The spatial electron distribution function is significantly expanded compared with the thickness of the cathode due to the topography of the electric field and space charge forces. Представлено результати чисельного моделювання динаміки електронного пучка в потужнострумовому діоді з ножовим катодом, який працює в режимі автоелектронної емісії. Чисельні моделювання були виконані методом макрочастинок в електростатичному наближенні. Показано, що існують два режими роботи діода. У першому режимі просторовий заряд у діодному проміжку малий. У цьому випадку анодний струм невеликий, а його величина визначається законом Фаулера-Нордгейма. Цей режим при збільшенні різниці потенціалів між катодом і анодом переходить у режим обмеження струму діода просторовим зарядом. У цьому випадку анодний струм визначається законом Чайлда-Ленгмюра. Показано, що функція розподілу електронів за енергією біля анода практично монохроматична, із максимумом, який визначається різницею потенціалів між катодом і анодом. Функція розподілу електронів у просторі значно розширена порівняно з товщиною катода, що пояснюється топографією електричного поля в досліджуваній системі і дією сил об'є-много заряду. Представлены результаты численного моделирования динамики электронного пучка в сильноточном диоде с ножевым катодом, который работает в режиме автоэлектронной эмиссии. Численные моделирования были выполнены методом макрочастиц в электростатическом приближении. Показано, что существуют два режима работы диода. В первом режиме пространственный заряд в диодном промежутке мал. В этом случае анодный ток невелик, а его величина определяется законом Фаулера-Нордгейма. Этот режим при увеличении разности потенциалов между катодом и анодом переходит в режим ограничения тока диода пространственным зарядом. И тогда анодный ток определяется законом Чайлда-Ленгмюра. Показано, что функция распределения электронов по энергии у анода практически монохроматична, с максимумом, определяемым разностью потенциалов между катодом и анодом. Функция распределения электронов в пространстве значительно уширена по сравнению с толщиной катода, что объясняется топографией электрического поля в исследуемой системе и действием сил объемного заряда.